Dampak Pengembangan Objek Wisata Kebun Raya Massenrempulu Terhadap Tingkat Kesejahteraan Masyarakat: (studi pada: Desa Batu Mila, Kecamatan Maiwa, Kabupaten Enrekang) - Muhammad Nur Arif; Rudi Latief; Rusneni Ruslan (Journal of Urban Planning Studies, 2020)
Abstract. The purpose of this study was to determine the impact of the development of the Massenrempulu Botanical Garden tourist attraction on the level of community welfare in Batu Mila Village, Kec. Maiwa. Regency. Enrekang. The variables used consisted of 3 of them: (1) Livelihoods; (2) Income Level; (3) Business Opportunities ;. The analytical method used is in the form of descriptive analysis, with the tabulation method to determine the impact of the development of a tourist attraction.It is known that several variables are source of livelihood, level of income, business opportunity. Where from the results of the livelihood analysis, where there are several people who experience changes in their livelihoods and get additional livelihoods, at the income level where the community has increased along with changes in livelihoods and on business opportunities where people also feel a positive impact with the birth of new types of businesses. and community opportunities to be absorbed into labor in tourist objects.